H2 Activation by a (PNP)Ir(C6H5) Complex via the Dearomatization/Aromatization Process of the PNP Ligand: A Computational Study - Zeng, Guixiang; Guo, Yong; Li, Shuhua (Inorganic chemistry, 2009)
Density functional theory calculations have been carried out to explore the mechanism of the H2 activation by the (PNP)Ir(C6H5) complex. Our calculations show that the reaction is most likely to go though three steps. The first step (also the rate-determining step) involves the proton transfer from the benzylic position of the PNP ligand to the metal center to form an Ir(III) hydride intermediate, accompanied by the dearomatization of the PNP ligand. Second, H2 is coordinated to the metal of this Ir(III) intermediate to form a molecular hydrogen complex. Finally, the H−H bond is heterolytically cleaved to produce the final trans-dihydride product, in which the benzylic carbon is protonated, and the PNP ligand is rearomatized. Thus, the H2 activation by the Ir(I) complex actually involves an Ir(III) hydride complex as a key intermediate. The Ir center and the PNP ligand cooperate in a synergistic manner in the H2 activation process. The above molecular mechanism could provide reasonable explanations for known experimental facts.